Drought alleviation efficacy of a galactose rich polysaccharide isolated from endophytic Mucor sp. HELF2: A case study on rice plant - Santra, Hiran Kanti; Banerjee, Debdulal (Frontiers in Microbiology, 2023)
Endophytes play a vital role in plants’ growth under biotic and abiotic stress conditions. In the present investigation, a Galactose-Rich Heteropolysaccharide (GRH) with a molecular weight of 2.98 x 105 Da was isolated from endophytic Mucor sp. HELF2, a symbiont of East Indian screw tree- Helicteres isora. OVAT (One Variable at A Time) experiment coupled with RSM (Response Surface Methodology) study exhibited 1.5-fold enhanced GRH production (20.10 g L-1) in supplemented potato dextrose broth at a pH of 7.05 after 7.5 days of fermentation in 26 °C. GRH has alleviated drought stress (polyethylene glycol induced) in rice seedlings (Oryza sativa ssp. indica MTU 7093 swarna) by improving its physicochemical parameters. It has been revealed that spray with a 50-ppm dosage of GRH exhibited an improvement of 1.58, 2.38, 3, and 4 times in relative water contents and fresh weight of the tissues, root length, and shoot length of the rice seedlings respectively. Moreover, soluble sugars, prolines, and chlorophyll contents of the treated rice seedlings were increased upto 3.5 (0.7±0.05 mg/g fresh weight), 3.89 (0.57 ±0.03 mg/g fresh weight) and 2.32 (1119±70.8 µg/gm of fresh weight) fold respectively, whereas malondialdehyde contents decreased up to 6 times. The enzymatic antioxidant parameters like peroxidase and superoxide dismutase and catalase activity of the 50 ppm GRH treated seedlings were found to be elevated 1.8 (720±53 unit/gm/min fresh weight), 1.34 (75.34±4.8 unit/gm/min fresh weight), and upto 3 (100 ppm treatment for catalase – 54.78±2.91 unit/gm/min fresh weight) folds respectively. In this context, the present outcomes contribute to the development of novel strategies to ameliorate drought stress and could fortify the agro-economy of our country.